Latent profiles and influencing factors of sleep quality in patients with chronic obstructive pulmonary disease - Li, Jing; Zhou, Na; Li, Xinxia (Frontiers in Medicine, 2025)
ObjectiveThis study aims to elucidate the classification characteristics and determinants of sleep quality in individuals with chronic obstructive pulmonary disease (COPD) to inform tailored interventions.MethodsA total of 231 COPD patients were selected using convenience sampling from January to June 2025 at the respiratory and critical care department of a tertiary hospital in Inner Mongolia. Data were collected through a general questionnaire, Pittsburgh Sleep Quality Index, COPD Assessment Test, and Self-Efficacy for Managing Chronic Disease 6-Item Scale. Latent profile analysis was employed to categorize sleep quality, and logistic regression was conducted to identify factors influencing each profile.ResultsSleep quality among COPD patients exhibited three distinct categories: better sleep group (40.6%), low efficiency-maintenance group (46%), and high hypnotic-use with daytime dysfunction group (13.4%). Sex, COPD Assessment Test score, and self-efficacy score were found to influence sleep quality in COPD patients.ConclusionThere is population heterogeneity in sleep quality among patients with COPD. Special attention should be given to individuals with low efficiency-maintenance and high hypnotic-use with daytime dysfunction groups to implement targeted interventions aimed at enhancing sleep satisfaction and overall quality of life.